Carbon stored in different coffee agroforestry systems in Huatusco, Veracruz, Mexico - Masuhara, Aiko (2015)
The effects of global warming are well known throughout the world. Carbon’s (C) capture potential is significant in the agricultural and forestry sectors. Agro-forestry systems have a strategic advantage in regards to the use of C, due to the potential content found in multiple plant species coexists simultaneously. The general object of the present study was the determination of carbon stock of the aerial stratums and soil in different land use system in Huatusco, Veracruz.. Results indicate that cloud forest (BMM) contains the largest contain of total C which was 481 Mg ha-1  and that the agroforestry systems contained a smaller quantity of total C and traditional intercropping system -coffee with multiple use trees- PTR (188 Mg ha -1 ) and specialized system - monoculture coffee with shade tree of Inga- ESP (133 Mg ha-1). C values in the aerial biomass were higher in the BMM. The contents of soil organic carbon (SOC) at depth of 0 to 60 cm were 117 Mg ha -,1 154 M-1 g ha and 128 Mg ha-1 in ESP, PTR and BMM, respectively. The largest percentage of SOC with regard to the total of each system was registered in the agroforestry systems with 88 % in ESP and 82 % in PTR, meanwhile BMM only had a 27% intake